Nursing cooperation of robot-assisted laparoscopic partial nephrectomy through retroperitoneal approach (经后腹腔入路达芬奇机器人肾部分切除术的护理配合) - ZHANG Han (张含); LIN Li (林丽); DONG Kui (董奎); LIU Qing (刘青) (中西医结合护理)
Objective To summarize the nursing cooperation of 62 patients undergoing Da Vinci robotic partial nephrectomy through retroperitoneal approach, and to provide reference for the formulation of standardized nursing coordination for this operation. Methods The clinical data of 62 patients who underwent Da Vinci robotic partial nephrectomy through retroperitoneal approach were retrospectively analyzed, the satisfaction of doctors and patients with nurses in the operating room was evaluated respectively, and the key points of perioperative nursing coordination were summarized. Results Totally 62 patients successfully completed the operation according to plan, no conversion to laparotomy, no change of operation mode, no serious complications occurred. The satisfaction of doctors (100. 00%) and patients(98. 39%) with operating room nurses was ideal. Conclusion Da Vinci partial nephrectomy through retroperitoneal approach has the advantages of safety and simplicity. Perfect preoperative nursing preparation and intraoperative nursing cooperation, especially special postural nursing play an important role in ensuring the smooth operation and preventing surgical complications. (目的 总结经后腹腔入路行达芬奇机器人肾部分切除术的手术护理配合要点, 以为制定该手术标准化护理配合提供参考依据。方法 回顾性分析2021年09月—2022年12月行后腹腔入路达芬奇机器人肾部分切除术的62 例患者的相关临床资料, 总结围手术期护理配合要点。结果 62例患者均顺利按计划完成手术, 无中转开腹, 未改变手术方式, 无严重并发症发生; 医生对手术室护士的满意度100. 00%(62/62), 患者对手术室护理满意度98. 39%(61/62)。结论 经后腹腔入路行达芬奇肾部分切除术具有安全、简便等优点, 完善的术前护理准备、术中护理配合特别是特殊的体位护理在保证手术顺利进行、预防手术并发症方面具有重要作用。)